Formation Of Trihalomethanes In Surface Water And Groundwater By Using Chlorine And Chlorine Dioxide As Disinfectant - Halid, Nur Fatin Hanani Mohd (Universiti Sains Malaysia, 2017)
Water is an important element for human and environment. Water pollution in drinking water which was caused by viruses, bacteria, pathogens and microorganisms need to be treated before being distributed to the consumers. Disinfection is one of the important process in treating water to kill microorganisms. Disinfection process causes the formation of disinfection by products (DBP) which affect the quality of drinking water and can harm human health due to its carcinogenic. The use of other disinfectant such as chlorine dioxide can also be used to kill microorganisms in water. Therefore, this study was carried out to compare the formation of trihalomethanes using chlorine and chlorine dioxide as water disinfectants and to find the relationships between chlorine and chlorine dioxide to pH. Based on the study, chlorine is found out to formed high trihalomethanes compared to chlorine dioxide. Based on the study on the groundwater samples, the maximum TTHM were found at pH 7 in the contact time of 24 hours with the value of 49.4 μg/L with the used of chlorine as disinfectants, while the minimum value of trihalomethanes found is also at pH 7 in the contact time of 3 hours with the used of chlorine dioxide as the disinfectants with the value of 5.4 μg/L. The relationships of disinfectants used in this study to pH does not shows a strong relationship since there were different fall and increment of total trihalomethanes at every pH.